2019
DOI: 10.1186/s13014-019-1347-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of carbon ion radiotherapy and transarterial chemoembolization treatment outcomes for single hepatocellular carcinoma: a propensity score matching study

Abstract: Background We compared clinical outcomes of carbon ion radiotherapy and transarterial chemoembolization in the treatment of hepatocellular carcinoma. Methods Data of 477 patients with hepatocellular carcinoma who had undergone carbon ion radiotherapy or transarterial chemoembolization between April 2007 and September 2016 were retrospectively reviewed. Treatment naïve patients with single HCC, who underwent carbon ion radiotherapy or transarterial chemoembolization as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Doses of 52.8-60 Gy in 4 fractions were used, with 60.0 Gy in 12 fractions close to the GI tract. Treatment with CIRT showed improved OS (88% vs. 58%), LC (80% vs. 26%), and PFS (51% vs. 15%) compared to TACE for single tumor HCC (71).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 97%
“…Doses of 52.8-60 Gy in 4 fractions were used, with 60.0 Gy in 12 fractions close to the GI tract. Treatment with CIRT showed improved OS (88% vs. 58%), LC (80% vs. 26%), and PFS (51% vs. 15%) compared to TACE for single tumor HCC (71).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 97%
“…Because Gy (RBE) is calculated based on the survival response of human salivary gland cells after C-ion beam irradiation, and not of liver cells, a direct comparison between Gy (RBE) and Gy for the liver can be problematic; moreover, the dose constraints of C-ion RT and those of IMRT for the liver might be different. However, the dose constraints of C-ion RT for the liver used in our study are considered safe, as previous clinical studies of C-ion RT used the same dose constraints, and no severe toxicities were observed [7][8][9][10][11].…”
Section: A Number Of Studies Have Investigated the Relationships Betwmentioning
confidence: 67%
“…Particle therapy has since improved radiation dose distributions further still [5,6]. In particular, carbon ion RT (C-ion RT) has produced favorable clinical outcomes for patients with HCC [7][8][9][10][11], as this modality reduces the dose to the liver while ensuring good target coverage [12,13] owing to its physical characteristics that include distal tail-off because of a high and narrow Bragg Peak as well as a sharp lateral penumbra [14]. Abe et al's dosimetric comparison between C-ion RT and SBRT for HCC treatment found that the former has better sparing of the liver [5].…”
Section: Introductionmentioning
confidence: 99%
“…One study [40] showed that for HCC patients receiving CIT or TACE, patients in the CIT group were significantly better than those in the TACE group in terms of 3-year OS, PFS and local control rates.…”
Section: Discussionmentioning
confidence: 99%